Hodnocení konkurenceschopnosti visegrádské čtyřky prostřednictvím aplikace CCR vstupově orientovaného modelu analýzy obalu dat - Staníčková, Michaela; Melecký, Lukáš (Univerzita Pardubice, 2011)
The paper deals with an application of Data Envelopment Analysis (DEA) to Visegrad Four (V4) countries and their NUTS 2 regions. The aim of the paper is to analyze a competitive potential of V4 countries and their regions by quantitative efficiency analysis. DEA method becomes a suitable tool for setting a competitive/uncompetitive position of each V4 country and NUTS 2 region within the Visegrad Group. The DEA method used for this evaluation is directly applied to the group of V4 countries and NUTS 2 regions based on a particular set of input and output indicators. The inputs and outputs form the key elements of the system evaluated for every country and region in the sense of their effective/ineffective economic position. In the first step, the economic efficiency of the countries and regions will be considered, in the second one, comparison of the competitive potentials of the countries and regions will be provided. National and regional efficiency is thus the mirror of competitiveness.
Keywords: V4 countries; NUTS 2 region; efficiency; data envelopment analysis; competitiveness; competitive potential; CCR input oriented model CRS